Obesity reduces the pro-angiogenic potential of adipose tissue stem cell-derived extracellular vesicles (EVs) by impairing miR-126 content: impact on clinical applications - Togliatto, G; Dentelli, P; Gili, M; Gallo, S; Deregibus, C; Biglieri, E; Iavello, A; Santini, E; Rossi, C; Solini, A; Camussi, G; Brizzi, M F (International Journal of Obesity, 2016)
Background/Objectives: Soluble factors and cell-derived extracellular vesicles (EVs) are crucial tissue repair mediators in cell-based therapy. In the present study, we investigate the therapeutic impact of EVs released by adipose tissue-derived stem cells (ASCs) recovered from obese subjects’ visceral and subcutaneous tissues. Methods: ASCs were recovered from 10 obese (oASCs) and 6 non-obese (nASCs) participants and characterized. In selected experiments, nASCs and oASCs were cultured with palmitic acid (PA) or high glucose (HG), respectively. EVs from obese (oEVs) and non-obese (nEVs) subjects’ visceral and subcutaneous ASCs were collected after ultracentrifugation and analyzed for their cargo: microRNA-126 (miR-126), vascular endothelial growth factor (VEGF), and matrix metalloproteinase 2 (MMP-2), and for their biological effects on endothelial cells (ECs). Western blotting analysis and loss- and gain-of function experiments were performed. Results: oEVs show impaired angiogenic potential compared with nEVs. This effect depends on EV cargo: reduced content of VEGF, MMP-2 and, more importantly, miR-126. We demonstrate, using gain- and loss-of-function experiments, that this reduced miR-126 content leads to Spred1 upregulation and the inhibition of the extracellular signal–regulated kinase 1/2 mitogen-activated protein kinase pathway in ECs. We also show that PA treatment of nASCs translates into the release of EVs that recapitulate oEV cargo. Moreover, HG treatment of oASCs further reduces miR-126 EV content and EV-mediated in vitro angiogenesis. Finally, impaired pro-angiogenic potential is also detected in EVs released from obese subcutaneous adipose tissue-derived ASCs. Conclusions: These results indicate that obesity impacts on EV pro-angiogenic potential and may raise concerns about the use of adipose tissue-derived EVs in cell-based therapy in the obese setting.